Photonics-Assisted Broadband Distributed Coherent Aperture Radar for High-Precision Imaging of Dim-Small Targets - Xuedi Xiao; Shangyuan Li; Xiaoxiao Xue; Luhang Xing; Shaowen Peng; Xiaoping Zheng; Bingkun Zhou (IEEE Photonics Journal)
High-precision imaging of dim-small target is demonstrated using a photonics-assisted broadband distributed coherent aperture radar (DCAR). The photonics-based methods lead to a high resolution, making it possible to discriminate small targets. In addition, the cooperative work of multiple radars enhances the signal-to-noise ratio (SNR) and helps to improve the imaging precision. Experimentally, the inverse synthetic aperture radar (ISAR) coherent imaging for a small unmanned aerial vehicle is conducted by a two-unit X-band DCAR (8–12 GHz), and the range and cross-range resolution are ∼3.4 cm and ∼3.6 cm, respectively. About 8.5 dB image SNR gain can be achieved in full-coherence mode compared to that in monostatic mode. Taking advantage of the SNR gain, the scatters that are below the noise floor when in monostatic mode can be clearly seen when full-coherence is realized, which reveals that the proposed photonics-assisted DCAR improves the imaging precision and makes it easier to identify dim-small targets.